(untitled) (Research, Society and Development, 2021)
Objective: Culturally adapt the Cornell Musculoskeletal Discomfort Questionnaire (CMDQ) to Brazilian Portuguese and assess content validity. Method: Methodological study. The five steps proposed by the literature for cultural adaptation were adopted. To analyze the data from the expert committee evaluation, the content validity index (CVI) and the Content Validity Coefficient per item (CVCi) were calculated considering values ​​above 0.80 and 0.78, respectively. Results: The CMDQ was submitted for translation into Portuguese by two independent translators. Based on the two translated versions, a consensual version was developed which was subjected to a back-translation. The translated versions, the consensual version in Portuguese and the back-translated versions were submitted for evaluation by a committee composed of five experts. After analysis by the expert committee, the total CVI of the questionnaire was 0.78. Seven items had CVCi below 0.78 (range 0.68 to 0.76). For the evaluation, all the recommendations of the committee were considered, and all the items indicated by the experts were changed. The changes in the items were made according to expert recommendations. All changes were made in the back-translated version of the CMDQ and resubmitted to the original author for approval of the final version. Conclusions: The cultural adaptation stage of the CMDQ for Brazil was completed with relevant results. The process of cultural adaptation and validation of the CMDQ is underway, the pre-test stage and, later, the validation stage will be carried out in research.